Attitudes towards COVID-19 preventive measures: an Italian cross-sectional study. (20th October 2021) - Scampoli, P; Di Giovanni, P; Cedrone, F; D'Addezio, M; Di Martino, G; Meo, F; Staniscia, T
Abstract: Background: The outbreak of COVID-19 was declared Public Health Emergency of International Concern on the January 2020. During an infectious disease outbreak, non-pharmaceutical interventions are essential to delay an epidemic peak and to flatten the epidemic curve, in order to wait for vaccine development. Perception or beliefs may be essential in determining adherence to official recommendations. The aim of this study was to assess whether perceptions of COVID-19 and awareness of preventive strategies effectiveness were associated to behavioural changes. Methods: Web-based survey was performed in Italy between the 9 and the 15 March 2020. The survey contained six sections: subject's demographics, subject's behaviours during the latest three weeks, subject's behaviours during the latest 24 hours, perceived efficacy of behaviours, awareness raised by the government-led prevention campaign for COVID-19 and co-occurring anxiety. Results: 1912 participants were enrolled in the study. 48.1% of the participants (n = 919) reported to perform at least 7 preventive behaviours. Most people reported a change in the frequency of their hand-washing (94.7%), an increment in the frequency of surface cleaning and disinfecting (58.9%), and a reduction in the use of public transport (92.5%). Behavioural changes were related to an increase in the anxiety level (OR 1.47; 95%CI 1.16-1.87). After adjusting for personal characteristics and anxiety, an association resulted between clear perception of COVID-19 high infectiousness (OR 1.25; 95%CI 1.00-1.59) and of its severe consequences (OR 1.29; 95%CI 1.05-1.59), clearness of communication about the virus (OR 1.41; 95%CI 1.17-1.71), and increased likelihood of performing the recommended behavioural changes. Conclusions: To better protect people against future epidemics, health-promotion efforts should be aimed at increasing the level of awareness towards infectious diseases and at implementing and encouraging non-pharmaceutical interventions. Key messages: Clear perception of COVID-19 high infectiousness and of its severe consequences are associated with an increased likelihood of performing the recommended behavioural changes. Health promotion strategies should be a critical part of infection prevention and control program.